2005
DOI: 10.1074/jbc.c500234200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Novel FAD-, FMN-, and ATP-containing l-Proline Dehydrogenase Complex from Pyrococcus horikoshii

Abstract: Two novel types of dye-linked L-proline dehydrogenase complex (PDH1 and PDH2) were found in a hyperthermophilic archaeon, Pyrococcus horikoshii OT3. Here we report the first crystal structure of PDH1, which is a heterooctameric complex (␣␤) 4 containing three different cofactors: FAD, FMN, and ATP. The structure was determined by x-ray crystallography to a resolution of 2.86 Å. The structure of the ␤ subunit, which is an L-proline dehydrogenase catalytic component containing FAD as a cofactor, was similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 26 publications
0
38
0
1
Order By: Relevance
“…For example, PDH1 is an (␣␤) 4 hetero-octameric complex with the ␤ subunit binding an FAD cofactor and exhibiting PRODH activity (6). The crystal structure of PDH1 shows that the FAD-binding domain has a Rossmann dinucleotide-binding fold similar to that of monomeric sarcosine oxidase, which is a member of the glutathione reductase family (6). As expected for a Rossmann fold protein, the FAD of PDH1 is highly extended, and the pyrophosphate interacts with a glycine-rich loop and associated conserved water molecule (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PDH1 is an (␣␤) 4 hetero-octameric complex with the ␤ subunit binding an FAD cofactor and exhibiting PRODH activity (6). The crystal structure of PDH1 shows that the FAD-binding domain has a Rossmann dinucleotide-binding fold similar to that of monomeric sarcosine oxidase, which is a member of the glutathione reductase family (6). As expected for a Rossmann fold protein, the FAD of PDH1 is highly extended, and the pyrophosphate interacts with a glycine-rich loop and associated conserved water molecule (45).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the bacterial enzymes have shown that PRODH is an FAD-dependent enzyme with a (␤␣) 8 barrel catalytic core (3,4), and P5CDH is an NAD ϩ -dependent Rossmann fold enzyme featuring a nucleophilic Cys (5). These enzymes are unrelated in sequence and structure to hyperthermophilic archaeal proline catabolic enzymes, which appear in unique hetero-tetrameric and hetero-octameric complexes (6).…”
mentioning
confidence: 99%
“…First, L-PDH of Thermococcus profundus (Tp/L-PDH) forms a complex consisting of four different subunits with molecular masses of 54 (␣), 42 (␤), 19 (␥), and 11 kDa (␦), respectively, with a heterotetrameric structure of ␣␤␥␦ containing two FADs (in ␣-and ␤-subunits) (8). Second, L-PDH isozyme 1 of Pyrococcus horikoshii (Ph/L-PDH1) consists of two different subunits with molecular masses of 56 (␣) and 43 kDa (␤) with a heterooctameric structure of ␣ 4 ␤ 4 containing one FAD (␤), one FMN (between ␣-and ␤-subunits), and one ATP (␣) (9,10). P. horikoshii also possesses L-PDH isozyme 2 (Ph/L-PDH2), which is similar to Tp/L-PDH.…”
mentioning
confidence: 99%
“…The main chain coordinates of the ApeLPDH monomer were essentially the same as those of the PDH1 ␤-subunit (PDH1␤) (Protein Data Bank code 1Y56-B) (11). Superposition of PDH1␤ onto ApeLPDH yielded a root mean square deviation (r.m.s.d.)…”
Section: Structural Comparison Of Monomeric Apelpdh and Pdh1␤-mentioning
confidence: 99%
“…The PDH1 hetero-octamer reportedly assembles as a tetramer of the ␣␤-heterodimer, within which one (␣␤) 2 block generated by an intermolecular disulfide bridge (formed between the two ␣-subunits) binds with another at the back to form the (␣␤) 4 -hetero-octamer (Fig. 6A) (11). Within the hetero-octamer, ␤-subunits interact only with ␣-subunits, and one molecule of FMN is located at the interface between the ␣-and ␤-subunits (Fig.…”
Section: Structural Comparison Of Monomeric Apelpdh and Pdh1␤-mentioning
confidence: 99%